Sugar-linked biodegradable polymers: regio-specific ester bonds of glucose hydroxyls in their reaction with maleic anhydride functionalized polystyrene and elucidation of the polymer structures formed - Galgali, P.; Agashe, M.; Varma, Anjanikumar (Carbohydrate Polymers, 2007)
In the development of sugar-linked synthetic polymers as biodegradable polymers, it is imperative to know the variety of polymer structures formed by the reaction of a multi-functional sugar molecule with the functionalized synthetic polymer on which the sugar is to be anchored. Enzymes produced by the microorganisms causing the polymer to biodegrade can be sensitive to the particular type of sugar hydroxyl utilized (such as anomeric, primary, or secondary hydroxyl group) for getting anchored to the polymer. In this paper, we present synthesis of regio-specific ester derivatives of glucose with anhydride, functionalized polymers, i.e., ester formation specifically with the anomeric, primary or secondary hydroxyls of glucose. Characterization of these different esters groups was done using FTIR spectroscopy; each ester peak was further deconvoluted to yield its different components. For this purpose, we studied the reactions of D-glucose, 6-O-trityl glucose, methyl glucoside, 1,2-5,6-diisopropylidene-D-glucose, and 1,2,3,4-tetraacetyl-D-glucose with maleic anhydride functionalized polystyrene (PSMAH). In this study, the primary hydroxyl of glucose was found to be even more reactive than the anomeric hydroxyl. The peaks at similar to 1716, similar to 1725, and 1729-1737 cm(-1) were assigned to the ester carbonyl of the anomeric, primary, and secondary hydroxyls of glucose (C2, C3, and C4), respectively. An attempt was made to quantify the extent to which the different polymer structures are formed in a particular reaction by taking ratios of non-variable reference peaks (polystyrene peak at 1493 cm-1) and variable peaks caused by the reaction (the residual anhydride carbonyl at 1780 cm(-1)). (c) 2007 Published by Elsevier Ltd.
Keywords: Biodegradable polymers; functionalized synthetic polymer; glucose; regio-specific; sugar-linked polystyrene

Polystyrene/TiO2 composite electrospun fibers as fillers for poly(butylene succinate-co-adipate): Structure, morphology and properties - Neppalli, Ramesh; Causin, Valerio; Benetti, Edmondo Maria; Ray, Suprakas Sinha; Esposito, Antonella; Wanjale, Santosh; Birajdar, Mallinath S.; Saiter, Jean-Marc; Marigo, Antonio (European Polymer Journal, 2014)
In this work, composite polystyrene/titanium dioxide (PS/TiO2) electrospun fibers were used as a reinforcement for a poly(butylene succinate-co-adipate) (PBSA) matrix. The structure, morphology, mechanical properties and degradation behavior of such materials were investigated, finding that, as a function of their TiO2 content, the fibers exerted different effects. The main mechanism through which the fibers modified the structure and morphology of the polymer matrix is by altering its crystallization kinetics. The presence of TiO2 modified the roughness of the fibers and therefore affected the interfacial adhesion between the filler and the matrix. The modulus of PBSA was improved, even though the brittleness of the materials was increased by the presence of the fibers. Different amounts of TiO2 within the fibers allowed to tune the hydrolytic degradation rate of the composites. This paper shows the potential of using composite electrospun fibers as effective fillers for the preparation of polymer-based composites. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymers; Degradation; electrospinning; Morphology; Nanocomposites; Polycaprolactone